2017
DOI: 10.1016/j.jjcc.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Anti-troponin antibodies following myocardial infarction

Abstract: Recent improvements in medical and surgical coronary revascularization techniques have significantly improved outcomes for patients with acute myocardial infarction (MI). However, large infarctions are often followed by a poorly understood process of pathological ventricular remodelling, which fails to return the heart to its premorbid state. Although it remains incompletely understood, there is increasing interest in the role of the immune system in this process. One hypothesis is that released cardiac protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…9 This is consistent with studies indicating a 0–27.6% prevalence of cardiac troponin autoantibodies, depending on underlying cardiac disease. 10 The pretest probability based on clinical information and local prevalence will determine how PEG, the discrepancy between assays, or other macrotroponin detection methods is most helpful in the local setting.…”
Section: Discussionmentioning
confidence: 99%
“…9 This is consistent with studies indicating a 0–27.6% prevalence of cardiac troponin autoantibodies, depending on underlying cardiac disease. 10 The pretest probability based on clinical information and local prevalence will determine how PEG, the discrepancy between assays, or other macrotroponin detection methods is most helpful in the local setting.…”
Section: Discussionmentioning
confidence: 99%
“…Evermore sensitive assays for cardiac troponins have demonstrated that these biomarkers may be detectable in several clinical conditions, as well as in a significant proportion of healthy subjects (59,60). Anticardiac troponin autoantibodies have also been described in different settings (namely in healthy subjects and after MI) (6). Although the possible role of autoimmunity mediated by autoantibodies against cardiac troponin has raised interest, this phenomenon has still not been fully elucidated (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Given these data, and the fact that there are still gaps in our knowledge, especially concerning remodelling mechanisms (6,39), a reappraisal of anti-cardiac troponin autoantibodies in this setting seems important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Fan et al also reported that cTnIAAbs are independent predictors of left ventricular remodelling in patients with ST-elevation myocardial infarction [8]. Due to the unknown mechanisms underlying these effects, the clinical relevance for cTnIAAb positive AMI patients remained unclear [9]. However, findings reported by Wu et al, who identified cTnIAAb to be involved in apoptosis, could explain the negative effects observed for cTnIAAb positive patients.…”
mentioning
confidence: 99%